Physical modeling of seismic source generation in failure of fault asperities; Physical Mesomechanics; Vol. 17, iss. 4 - Ruzhich V. V.; Psakhie S. G. Sergey Grigorievich; Chernykh E. N.; Shilko E. V.; Levina E. A.; Ponomareva E. I. (2014, 2014)
Title screen